Constitutional Approach as a Factor of Sports Injury Prevention - Tatyana V. Kulemzina; Svetlana V. Krasnozhon; Alexander V. Shakula (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
A career in professional sports depends on a number of factors related both directly to the athlete's body and to the influence of external factors. Age, sport, health, personal trainer, training conditions, etc. - all this is important to achieve the result. However, the athlete's constitutional features are significant and fundamental for achieving the result. These are not just morphological signs, but also a tendency to the occurrence of injuries and individual psychological characteristics as well as their correspondence to the functional capabilities of the athlete's body. It is the individual mental characteristics that determine the type of response to the result of the competition (especially negative), the motivational aspect for achieving the result and recovering from injuries. This is important, since injuries are one of the primary problems of sports (regardless of the type), and the number of injuries and traumatological pathologies reaches 44% of the total number of nosologies. Aim. To substantiate the possibility and expediency of using integrative medicine methods in the rehabilitation treatment of sports injuries of the ankle joint. Material and methods. The research object was 38 male athletes involved in game sports, 18 - 26 years old with moderate ankle injuries, sports experience - 10 - 18 years, sports qualifications from the 1st category to the master of sports (MS). The patients were randomly divided into two groups. In the main group - 20 athletes - the rehabilitation schemes included: classical acupuncture, homotoxicology, hirudotherapy, post-isometric relaxation. To comfortably accompany the recovery process, a collegial model of the relationship between a doctor and an athlete was used. The control group consisted of 18 athletes with applied standard recovery rehabilitation scheme. Results and discussion. In athletes in both groups, the clinical manifestations of the disease were stopped at the same time (within6-8 days). Functional recovery of the injured joint in the main group was observed by the 16th day, in the control group - by the 22nd day. Athletes of the main observation group started competitive activity on average after 23 days, in the control group - after 28 days. Conclusion. The use of integrative medicine methods in athletes allowed to shorten the recovery period, reduce the dosage of painkillers, sedatives, anti-inflammatory drugs, accelerate the psychological adaptation of the athlete to the changed life situation and provide relief for injured athletes to undergo rehabilitation treatment, practically preserving overall physical performance.